ANALYSIS OF FAMILY NURSING CARE WITH THE IMPLEMENTATION OF BRISK WALKING EXERCISE ON CLIENTS HYPERTENSION TO OVERCOME MANAGEMENT INEFFECTIVE HEALTH IN THE TANDES AREA - Wulandari, Dhian; Rusdianingseh; Nety Mawarda Hatmanti; Chilyatiz Zahroh (Universitas Nahdlatul Ulama Surabaya, 2023)
Background: Hypertension sufferers who rarely exercise, smoke, consume alcohol, are overweight, cannot manage stress, often stay up late, do not comply with taking medication and eat whatever they want without paying attention to salt intake can cause uncontrolled blood pressure which can lead to hypertension complications and even death. This behavior is an ineffective health management caused by lack of exposure to information related to hypertension and ineffective health care patterns in the family. Objective: The aim of this research is to analyze family nursing care by applying brisk walking exercise to hypertensive clients to overcome ineffective health management in the Tandes Subdistrict, Surabaya. Methods: The research design used a case method with the subject used being 1 patient with ineffective health management nursing problems. The research was conducted in the Tandes area for 2 weeks with data collection methods including assessment. diagnosis, intervention, action and evaluation. Result: The results of case studies on hypertensive clients with ineffective health management nursing problems show that after being given nursing care therapy by implementing 5 family tasks using a modified brisk walking exercise, the results of improved health management were obtained, which was indicated by the client and family understanding more about hypertension (understanding, risk factors, signs of symptoms and diet), the client's body looks fitter, the client's blood pressure which was initially 170/100 mmHg at the time of the assessment gradually dropped to 140/90 mmHg, the client began to pay attention to diet, the family was willing to help with treatment and took the client for control to a health facility nearest. Conclusion: Evidence based nursing implementation of brisk walking exercise which is carried out with a training frequency of 3 times a week, for 15-30 minutes with an average walking speed of 4-6 km/hour is shown to be effective in reducing ineffective health management.